Electronic Marketing in a Pandemic with Respect to the Impact of Technology and Business Adaptation - Al Muala, Ayed Moh’d; Alzyadat, Akef Yousef; Al-Ababneh, Hassan Ali; Ananzeh, Husam; Al Kurdi, Barween; Ibragimkhalilova Тatyana; Barhoush, Fawaz Mohd Salim (International Review of Management and Marketing, 2025)
The purpose of this article is to study the transformation of electronic marketing caused by the COVID-19 pandemic, with an emphasis on the impact of technology and innovation on business adaptation. The acceleration of the implementation of digital tools in marketing strategies by the pandemic crisis is substantiated, and the technologies that have become the main drivers of transformation are highlighted. The main objective of the study is to substantiate the trends in marketing transformation in the context of the pandemic, identify areas for the prompt adaptation of companies’ marketing strategies taking into account technologies and the use of extrapolation tools for short-term forecasting. The research methods include extrapolation of current digital marketing trends, analysis of the use of technologies and innovations, such as artificial intelligence, big data analytics and process automation, as well as their impact on changing consumer preferences and strategic management of companies. The importance of a prompt business response to changes in the market environment is emphasized, the effectiveness of extrapolation tools for forecasting consumer preferences and forming strategies is emphasized. The results obtained will allow companies to more effectively adapt their marketing efforts and use technology to increase business resilience in times of crisis.